Latin grooves Latin dance workout (Parkway, N.J. Peter Pan Industries, 2003)
A spicy combination of easy to follow dance steps that will have you moving from Mambos to Cha-Chas while burning fat and toning muscles in a 30 minute total body challenge.
Gloria Araya-Quinlan, Marianne Hoegl, Juel Bedford, Sabrina Pratt, Debbie Furhmen.
DVD (Regional coded, NTSC) ; Standard full frame (1.33:1) ; Single layer ; Dolby Digital.
In English/Spanish.
Keywords: Aerobic dancing; Dance in motion pictures, television, etc; Exercises for women